The dopaminergic system mediates the lateral habenula-induced autonomic cardiovascular responses - Sato, Yuma; Matsumoto, Masayuki; Koganezawa, Tadachika (Frontiers in Physiology, 2024)
The lateral habenula (LHb) has been implicated in stress coping and autonomic control. The LHb regulates the midbrain system of monoamine neurotransmitters such as dopamine, serotonin, and noradrenaline. However, how the LHb regulates autonomic cardiovascular control in stressful situations is unclear. In this study, we examined the participation of the midbrain dopaminergic system in the cardiovascular response elicited by activation of the LHb. We used urethane-anesthetized Wistar male rats. We performed electrical stimulation of the LHb to observe changes in heart rate and blood pressure. Stimulation of the LHb caused bradycardia and a pressor response. Application of a nonselective dopamine receptor antagonist attenuated both the heart rate and the blood pressure changes induced by the LHb. We also tested the effects of blockade of dopamine receptor subtypes in the LHb-induced cardiovascular responses. Application of selective dopamine D1/D5, D2/D3, or D4 receptor antagonists attenuated the LHb-induced pressor response but did not change the HR response. Furthermore, we examined the effect of inactivation of the ventral tegmental area (VTA) on the cardiovascular response induced by LHb stimulation. Inactivation of the VTA turned bradycardia into tachycardia caused by the LHb stimulation and attenuated the pressor response. Our results indicated that regulation of the dopaminergic system by the LHb mediates the generation of the autonomic cardiovascular response. Dopamine D1-like and D2-like receptors mediate the sympathoexcitation resulting from the activation of the LHb. The VTA is one of the dopaminergic origins related to the cardiovascular response originating from LHb activation.